Differentiated Learning Number Division Material Increases Elementary School Students' Interest and Learning Outcomes - Supartiningsih, Endang; Edi Wibowo, Setiawan (Universitas Pendidikan Ganesha, 2023)
Students' low interest and learning outcomes in learning mathematics are due to the need for more application of varied learning models, so in the learning process, students are more unfocused. The research aims to analyze the effect of differentiated learning on the interests and learning outcomes of fourth-grade elementary school students. This research is classified as experimental with a non-equivalent control group design. The subjects involved in this research were fourth-grade elementary school students. Data collection in this research was carried out using observation, interviews, questionnaires, and tests. Data regarding learning interest is collected using a questionnaire, and learning outcomes are measured using multiple-choice tests and essays. The data obtained in this research was then analyzed using the multivariate analysis technique analysis of variance (Manova). The results of the data analysis show that the first hypothesis, namely the null hypothesis, is rejected, and the alternative hypothesis is accepted. Next, the second hypothesis, namely the null hypothesis, is rejected, and the alternative hypothesis is accepted. The calculated F significance number is less than 0.05 in the third hypothesis, so the null hypothesis is rejected, and Ha is accepted. Based on these results, differentiated learning positively influences the interest and learning outcomes of fourth-grade elementary school students in learning mathematics. Differentiated learning can increase fourth-grade elementary school students' interest and learning outcomes.